Contribution to the genus Clypeocaenis Soldán, 1978 (Ephemeroptera: Caenidae) from Lao People’s Democratic Republic with a key to Oriental species - Vannachak, Viengkhone; Malzacher, Peter; Sangpradub, Narumon (Zootaxa, 2024)
Larvae of Clypeocaenis laosensis sp. nov. were collected from the Xe Nou River, Xe Bang Hieng River, and Tha Hao Stream in central and southern Lao PDR. This investigation also encompassed the examination of eggs extracted from female larvae, and we give here the first egg description of Cl. multisetosa Soldán, 1978 and Cl. oligosetosa Soldán, 1983. Clypeocaenis laosensis sp. nov. is closely related with Cl. gayathri Balasubramanian & Muthukatturaja, 2020 and Cl. kaveri Balasubramanian & Muthukatturaja, 2021. The new species is distinguishable from other Clypeocaenis species by specific morphological traits. These include the number of setae on the clypeus, the morphology of the labial palpus, the length of marginal setae on the middle and hind femora, setae of the transverse row on the forefemur, and body surface microtrichia. A detailed comparison of the morphological features between this new species and its closely related species is provided. Furthermore, the first-time reporting of Cl. multisetosa and Cl. oligosetosa in Lao PDR expands the known Caenidae diversity in the country to five species. A key to the nymphs of the Oriental species of Clypeocaenis is provided.